The Effect of Boron Impurity on the Structure and Mechanical Properties of Hafnium - S.V. Chornobuk; V.A. Makara; A.O. Goncharenko (Журнал нано- та електронної фізики)
In present study the influence of low concentrations (≤ 1.5 at. %) impurities of boron on the structure and mechanical properties of hafnium has been discussed. Experimental specimens of the alloys with different content of impurities of boron have been compacted during reaction hot syntering. Revealed significant dependence of structure and mechanical properties of these alloys on their composition. The prospective use of boron as an alloying element to improve the operational characteristics of hafnium has been shown.